Pectoral Dimorphism Is a Pervasive Feature of Skate Diversity and Offers Insight into their Evolution. Issue 1 (15th June 2019) - Martinez, C M; Kao, B H; Sparks, J S; Wainwright, P C
Synopsis: Mature skates (Batoidea: Rajoidei) display a unique form of sexual dimorphism in which males develop a concave anterior pectoral fin, giving them a bell-shaped appearance. Recent work has linked the male-specific transformation to differential skeletal development that is coincident with the rapid elongation of claspers, cartilage-supported intromittent organs. Still, little is known about the prevalence of pectoral dimorphism across skates or of interspecific variation in its expression. Here, we use various morphological approaches to broadly explore pectoral dimorphism in skates, with the goal of understanding its significance in their evolutionary history. We find that pectoral fin sexual dimorphism exists across skate diversity, positively identifying its presence in at least 131 species spanning 33 genera, approximately 40% of valid species. Further, we show that the nature of male–female shape change is largely consistent across species, but that it differs in its magnitude at a biologically meaningful scale. Finally, we use the pygmy skate Fenestraja plutonia as a case study to illustrate ontogenetic patterns in the development of pectoral fin dimorphism, additionally identifying sex-based differences in the pelvic girdle and jaw. Our work suggests that the diversity of pectoral dimorphism in skates is linked to comparative growth and maturation, and potentially to processes underlying reproductive and life history diversification within the group.